2022
DOI: 10.1039/d2cc01250b
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative coupling of silylated nonagermanide clusters

Abstract: Polyhedral main group element clusters of tetrel elements are discussed as suitable building units to form atom-precise nano-structures. Herein we report the oxidative coupling of two [Ge9{Si(TMS)3}2]2– clusters (TMS: trimethylsilyl)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…For example, mild oxidation of the Zintl anion Ge 9 4– generates the corresponding oligo- or polymers . Very recently, Fässler et al have reported the oxidative coupling of disilylated germanium cluster [Ge 9 (Hyp) 2 ] 2– (Hyp = Si­(SiMe 3 ) 3 ) affording a dimeric cluster [Ge 18 (Hyp) 4 ] 2– , which was identified by mass spectrometry . In our group, the metalloid germanium cluster [Ge 9 (Hyp) 3 ] − available in high yield by the reaction of Ge 9 4– with ClSi­(SiMe 3 ) 3 has been oxidized with FeCl 2 in the presence of diphenylphosphinoethane (dppe), resulting in a neutral Ge 18 (Hyp) 6 cluster A and the reduced Fe­(I) salt, [Fe­(dppe)]­[Ge 9 (Hyp) 3 ] .…”
Section: Introductionmentioning
confidence: 77%
“…For example, mild oxidation of the Zintl anion Ge 9 4– generates the corresponding oligo- or polymers . Very recently, Fässler et al have reported the oxidative coupling of disilylated germanium cluster [Ge 9 (Hyp) 2 ] 2– (Hyp = Si­(SiMe 3 ) 3 ) affording a dimeric cluster [Ge 18 (Hyp) 4 ] 2– , which was identified by mass spectrometry . In our group, the metalloid germanium cluster [Ge 9 (Hyp) 3 ] − available in high yield by the reaction of Ge 9 4– with ClSi­(SiMe 3 ) 3 has been oxidized with FeCl 2 in the presence of diphenylphosphinoethane (dppe), resulting in a neutral Ge 18 (Hyp) 6 cluster A and the reduced Fe­(I) salt, [Fe­(dppe)]­[Ge 9 (Hyp) 3 ] .…”
Section: Introductionmentioning
confidence: 77%
“…The same bonds in the naked cluster [Ge 9 −Ge 9 ] 6− are between 257 and 259 pm, 1 while those in the copper-capped silylated cluster are between 252 and 254 pm. 9 This elongation in the naked cluster can be explained by the larger amount of space that the nonbonding electrons at the capping atom need, compared to the space needed by the exobond to the hypersilyl ligand. This can also be observed at the open square on the opposite side of the cluster, which has one exobond between the Ge 9 moieties and in the case of 1 and 2 another exobond to the second ligand.…”
mentioning
confidence: 99%
“…Here, the dimer was structurally characterized as the [NHC iPr Cu] + adduct {NHC iPr Cu[Ge 9 (Hyp) 2 ]} 2 [NHC iPr = 1,3-di(isopropyl)imidazolylidine], while a dimeric anion [Ge 18 (Hyp) 4 ] 2− was only postulated on the basis of mass spectra. 9 The oxidizing agent in fact turned out to be very doubtful, since the reaction was carried out in the presence of Cy 2 BCl (Cy = cyclohexyl) and appeared to be mediated by trace amounts of oxygen. A byproduct, Cy 2 B−O−BCy 2 , was isolated instead of a reducing product.…”
mentioning
confidence: 99%
See 2 more Smart Citations